2009
DOI: 10.1002/hbm.20833
|View full text |Cite
|
Sign up to set email alerts
|

Priming words with pictures: Neural correlates of semantic associations in a cross‐modal priming task using fMRI

Abstract: In our everyday life we process information from different modalities simultaneously with great ease. With the current study we had the following goals: to detect the neural correlates of (1) automatic semantic processing of associates and (2) to investigate the influence of different visual modalities on semantic processing. Stimuli were presented with a short SOA (350 ms) as subjects performed a lexical decision task. To minimize the variance and increase homogeneity within our sample, only male subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 65 publications
3
26
2
Order By: Relevance
“…A rapid event-related fMRI (erfMRI) design was used to present related, unrelated, and nonword trials [Amaro and Barker, 2006;Gold et al, 2006;Kircher et al, 2009;Sass et al, 2009a,b;Whitney et al, 2009]. The idea behind the design was that the presentation of trials from the same condition in a sequence leads to a better sampling of the HRF curve and hence to a better signal.…”
Section: Fmri Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…A rapid event-related fMRI (erfMRI) design was used to present related, unrelated, and nonword trials [Amaro and Barker, 2006;Gold et al, 2006;Kircher et al, 2009;Sass et al, 2009a,b;Whitney et al, 2009]. The idea behind the design was that the presentation of trials from the same condition in a sequence leads to a better sampling of the HRF curve and hence to a better signal.…”
Section: Fmri Proceduresmentioning
confidence: 99%
“…The opposite contrast was calculated to obtain RS. To ensure, that the activations (RS) and deactivation (RE) were a result of the differences between the related and unrelated conditions and to asses only those voxels that are activated or deactivated in both conditions, all contrasts were exclusively masked with the nonword condition [e.g., Bright et al, 2004;Devlin et al, 2002;Kircher et al, 2009]. The mask was thresholded at P < 0.05 uncorrected.…”
Section: Fmri Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggested possible candidate regions for amodal processing of words and pictures, such as the ventral occipitotemporal cortex (Chao et al, 1999;Buckner et al, 2000;Seghier and Price, 2011), the posterior middle temporal gyrus (Chertkow et al, 1997;Vandenbulcke et al, 2007;Kircher et al, 2009), the angular gyrus (Bonner et al, 2013), the anterior temporal pole (Hodges et al, 1992;Vandenberghe et al, 1996;Rogers and McClelland, 2004;Patterson et al, 2007;Binder et al, 2009;Lambon Ralph et al, 2010), the left inferior frontal sulcus (Wagner et al, 1997), the anterior inferior frontal gyrus (Goldberg et al, 2007), and the left middle frontal gyrus (Demb et al, 1995;Vandenberghe et al, 1996;Van Doren et al, 2010). Part of the amodality, especially in left inferior frontal sulcus and ventral occipitotemporal transition zone, may be due to working memory (Badre et al, 2005;Van Doren et al, 2010) or executive control (Whitney et al, 2011) which is required by task regardless of input-modality.…”
Section: Introductionmentioning
confidence: 97%
“…In some cases, participants classified pairs of concepts as being taxonomically related, thematically related, or unrelated (Kriukova, Bridger, & Mecklinger, 2013;Maguire, Brier, & Ferree, 2010). In others, participants rated on a 7-point Likert scale the extent to which each pair is linked together in a common scenario or in a functional relationship (Jones & Golonka, 2012;Kalénine et al, 2012;Kircher, Sass, Sachs, & Krach, 2009). A slightly different validation approach was taken by Lin and Murphy (2001), who asked participants to write a sentence describing how two given concepts go together to form a category, and, then, on the basis of these responses, the authors categorized the pairs of concepts as thematic or taxonomic.…”
mentioning
confidence: 99%